Spectrum of Magnetic Resonance Spectroscopy (MRS) in Differentiating Paediatric Leukodystrophies in Pakistani Population - Zainab Riaz, Ania Javed, Humaira Riaz, Mehwish Tabassum, Saerah Iffat Zafar, Syeda Sanam Zahra, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of findings of MRS in differentiating paediatric leukodystrophies in Pakistani population. Study design: Cross sectional descriptive study. Place and duration of study: Armed Forces Institute of Radiology and Imaging, Military Hospital Rawalpindi from 25thAugust 2018 to 24th February 2019. Methodology: A total of 110 individuals who were coming in for an MRI test and were either male or female, older than one month of age, and younger than 12 years of age, were chosen. A 3.0T MRI scanner equipped with MRS techniques was used for each scan. Axial T1 and T2 Weighted spin-echo, FLAIR, coronal, and sagittal T2 Weighted spin-echo images were all part of the MRI imaging protocol. During the same session, a single section multivoxel 2D chemical shift spectroscopy sequence was also carried out. In MRS, the metabolites that were detected in each of our patients were choline, creatine, lactate, N-acetyl aspartate, and myo-inositol. Data were examined utilizing SPSS 21. Results: The average age was 5.24±1.89 year. 56 (50.91%) of the 110 patients were male children, compared to 54 (49.09%) female children, for a male to female ratio of 1.1:1. The following paediatric leukodystrophies were more often found with MRS in this study: Krabbes disease in 13 (11.82%), Canavan's disease in 19 (17.27%), Adrenoleukodystrophy in 41 (37.27%), Leigh disease in 25 (22.73%), and Metachromatic leukodystrophy in 12 (10.91%). Practical Implication: The underlying issue has recently been linked to mutations in the DARS2 gene, which codes for mitochondrial aspartyl-tRNA synthetase. Conclusion: MRS, which is more affordable than other existing tests, should be utilized in every patient with clinical leukodystrophies. Keywords: Leukodystrophies, Magnetic resonance spectroscopy, MRS